Absorption properties and forcing efficiency of light-absorbing water-soluble organic aerosols: Seasonal and spatial variability. (1st March 2021) - Choudhary, Vikram; Rajput, Prashant; Gupta, Tarun
Abstract: Light-absorbing organic aerosols, also known as brown carbon (BrC), enhance the warming effect of the Earth's atmosphere. The seasonal and spatial variability of BrC absorption properties is poorly constrained and accounted for in the climate models resulting in a substantial underestimation of their radiative forcing estimates. This study reports seasonal and spatial variability of absorption properties and simple forcing efficiency of light-absorbing water-soluble organic carbon (WSOC, SFE WSOC ) by utilizing current and previous field-based measurements reported mostly from Asia along with a few observations from Europe, the USA, and the Amazon rainforest. The absorption coefficient of WSOC at 365 nm ( b abs-365 ) and the concentrations of carbonaceous species at Kanpur were about an order of magnitude higher during winter than in the monsoon season owing to differences in the boundary layer height, active sources and their strengths, and amount of seasonal wet precipitation. The WSOC aerosols during winter exhibited ∼1.6 times higher light absorption capacity than in the monsoon season at Kanpur site. The assessment of spatial variability of the imaginary component of the refractive index spectrum ( k λ ) across South Asia has revealed that it varies from ∼1 to 2 orders of magnitude and light absorption capacity of WSOC ranges from 3 to 21 W/g. The light absorption capacity of WSOC aerosols exhibited less spatial variability across East Asia (5–13 W/g) when compared to that in the South Asia. The photochemical aging of WSOC aerosols, indicated by the enhancement in WSOC/OC ratio, was linked to degradation in their light absorption capacity, whereas the absorption Ångström exponent ( AAE ) remained unaffected. This study recommends the adoption of refined climate models where sampling regime specific absorption properties are calculated separately, such that these inputs can better constrain the model estimates of the global effects of BrC. Graphical abstract: Image 1